1988
DOI: 10.1071/bi9880387
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Short-term and Long-term Lithium Treatment on Uptake and Retention of 10dine-131 in Rat Thyroid

Abstract: No significant change occurred in the uptake by the thyroid of male Wistar rats of a standard dose of carrier-free 131 1 administered intraperitoneally and its retention by the thyroid, as measured by biological and effective half-life, after feeding these rats a powdered pelleted diet containing lithium carbonate (I .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 10 publications
2
11
0
Order By: Relevance
“…In this study, lithium when administered in the diet for up to 4 months showed a significant reduction in the thyroidal 131 I uptake after 2 h and 24 h which is in agreement with our earlier reports [16,23]. Lithium has previously been reported [29] to cause a marked decrease in the rate of synthesis of 131 I iodothyronines.…”
Section: Discussionsupporting
confidence: 95%
See 4 more Smart Citations
“…In this study, lithium when administered in the diet for up to 4 months showed a significant reduction in the thyroidal 131 I uptake after 2 h and 24 h which is in agreement with our earlier reports [16,23]. Lithium has previously been reported [29] to cause a marked decrease in the rate of synthesis of 131 I iodothyronines.…”
Section: Discussionsupporting
confidence: 95%
“…They also reported that when lithium treatment was prolonged for 6 months, no change was observed in the thyroidal 131 I uptake. The normalization of uptake under lithium conditions given for 6 months, as indicated in our earlier study [23], might be explained by the hypothesis of Sedvall et al [18], which indicates that 131 I uptake may be regulated by TSH. The increased T biol of 131 I in the thyroid following lithium treatment observed in the present study is supported by other authors [31] and resulted in the use of lithium as an adjunct to radioiodine therapy in thyrotoxic patients.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations